Beyond the Norm: Understanding Stigma in Sexual and Relational Minorities - Carvalho, A.; Aybar Camposano, G.; Rodrigues, D. L. (Exploring Identity, Diversity and Stigma in LGBTQ+ Lives, 2026)
Sexual and relational minorities encompass a broad spectrum of identities and relationship practices (i.e., agreements and expectations), including lesbian, gay, bisexual, transgender, queer, and other individuals from sexual and gender minorities (LGBTQ+), those within the asexual spectrum (a-spec), and people engaging in consensual non-monogamous relationships. This chapter explores how stigma impacts sexual and relational minorities, framing the discussion in the minority stress model. We examine external (distal) and internal (proximal) stressors to understand the mechanisms through which stigma operates. Special attention is given to the shared and unique challenges faced by sexual and relational minorities, and to the experiences of individuals in the a-spec, an underrepresented sexual minority. Finally, we discuss strategies to counteract stigma and foster resilience, emphasizing the need to challenge entrenched social norms. By advancing an understanding of these dynamics, this chapter contributes to the ongoing effort to create a more inclusive society that embraces diverse identities and relationships.